Application of DC distributed bus bar power systems on ships - Bezhik A. S.; Lebedev A. K.; Romanovsky V. V.; Vlasov A. B. (Vestnik MGTU)
Operation of vessels sailing along the Northern Sea Route is associated with numerous risks that determine increased requirements for the reliability of the propulsion system. In this regard, it is important to use ship electrical networks based on the distribution of direct current (DC) electricity, the operation of which provides a number of advantages in comparison with AC distribution systems. Conducting technical control of imported ship equipment due to the lack of information received from foreign manufacturers is an urgent need. Using the example of a propulsion electric plant with Azipod-type equipment, methods for assessing the technical condition of the propulsion electric motor, protecting the shaft from parasitic voltages and currents that can accelerate the destruction of bearings have been described. Methods for troubleshooting semiconductor elements included in the frequency converter have been considered. Probable errors in the operation of the nacelle position monitoring system have been presented. The possibilities of remote assessment of the technical condition of the system have been determined. The aim of the work is to develop stages of technical control and evaluation of the obtained parameters for the development of expert decisions on the operational reliability and prospects for further operation of equipment and elements in Azipod-type propulsion electric systems relevant on numerous vessels.